Impacts of inventory credit, input supply shops, and fertilizer microdosing in the drylands of Niger - Pender, John L.; Abdoulaye, Tahirou; Ndjeunga, Jupiter; Gerard, Bruno; Kato, Edward (International Food Policy Research Institute, 2008)
This study investigated the impacts of access to inventory credit, input supply shops, fertilizer microdosing demonstrations, and other factors on farmers’ use of inorganic fertilizer and other inputs in Niger and on crop yields. We found that access to inventory credit and input supply shops has increased the use of inorganic fertilizer and seeds and that microdosing demonstrations have increased the use of inorganic fertilizer. Ownership of traction animals and access to off-farm employment have also contributed to the use of inorganic fertilizer, while larger farms use less fertilizer and labor per hectare. The impacts of these interventions and technologies depend on the crop mix. Inorganic fertilizer has a positive impact on millet and millet–cowpea yields when applied using microdosing, with an estimated marginal value-cost ratio greater than 3 for those crops indicating significant profitability. By contrast, microdosing has a negative impact on yields of the millet–sorghum–cowpea intercrop, suggesting that microdosing should not be promoted when sorghum is part of the crop mix. However, better access to input supply shops has contributed to higher yields of the millet–sorghum–cowpea intercrop. The predicted effect of inventory credit on farmers’ income as a result of increased inorganic fertilizer use is an increase of 5,000 to 10,000 FCFA per hectare (about US$10 to US$20 per hectare in 2005) in millet or millet–cowpea production. Similarly, being 10 km closer to an input supply shop is predicted to increase farmers’ income by 3,200 to 4,500 FCFA per hectare. These benefits do not take into account the impacts of the interventions on seeds or other inputs, which are also generally positive. The positive impacts are linked to the use of fertilizer microdosing, which has increased the productivity of fertilizer use in millet and millet–cowpea production, indicating synergies among the various interventions. They are also linked to these specific crops, because we found less favorable impacts of these interventions for the millet–sorghum–cowpea intercrop and for peanuts. Other interventions that could help to boost the use of inputs and productivity include promotion of improved access to farm equipment and traction animals and promotion of higher-value crops such as hibiscus. Further research on these topics appears warranted. Research on the implications of interventions on land degradation would also be useful.-- Author's Abstract